Response of Two Rapeseed Cultivars (Brassica napus L.) in Terms of Growth Indices, Yield and Yield Components to Method of Nitrogen Fertilizer Application in Gonbad-e Qabus Plain - Seyyed Fazel Fazeli Kakhki; Morteza Goldani; Farhad Soleimani fard; Naser Bikzadeh (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
In order to investigate the response of rapeseed to the application method of nitrogen fertilizer, a factorial experiment was conducted in a randomized complete block design with three replications in the 2015-2016 crop season. The first factor was two canola cultivars (Hayola 401 and RGS003) and the second factor was four application method of nitrogen fertilizer treatment as F1: three stages fertilization in soil used, F2: three stages foliar spraying application, F3: four stages of fertilization in soil used and F4: four stages of fertilization as foliar spraying. The results showed that the highest plant height was obtained by applying F3 treatment with 144.8 and 161 cm per plant in the second and third sampling, respectively. The highest leaf dry weight and leaf area was obtain by application F3 treatment in all sampling stages. The same trend was observed for the dry weight of lateral branches, so that in the third stage of sampling, the highest dry weight of lateral branches with 59.4 g.plant-1 was obtained by consuming of F3 treatment. The highest biomass and grain yield were obtained from F3 treatment with 1029 g.m-2 and 332 g.m-2 respectively. The highest number of pod (145 pod per plant), biomass (1105 g.m-2), oil yield (121 g.m-2) and seed yield (358 g.m-2) was obtain from application F3 in Hayola 401 cultivar. In general, the results showed that all morphological and yield indices of the plant were obtained from application of nitrogen fertilizer in four stages at the soil used that Hayola 401 cultivar showed more positive response to this used method of fertilization.